Tracking the Activity of mTORC1 in Living Cells Using Genetically Encoded FRET‐based Biosensor TORCAR. Issue 4 (7th December 2016) - Zhou, Xin; Li, Simin; Zhang, Jin
Abstract: Mechanistic target of rapamycin complex 1 (mTORC1) is a highly conserved serine/threonine protein kinase that responds to multiple distinct signals (e.g., growth factors, amino acids, stress, and energy level) and coordinates cell growth and proliferation. The underlying molecular mechanisms by which these stimuli regulate the activity of mTORC1 are still not fully understood. The spatial compartmentalization of mTORC1 signaling has been suggested as an important mechanism for mTORC1 to achieve the signal specificity and efficiency. To examine the spatial regulation of the activity of mTORC1 in live cells, we describe a protocol using a newly developed molecular tool, a genetically encoded fluorescence resonance energy transfer (FRET)‐based mTORC1 activity reporter, TORCAR. When expressed in the cell, TORCAR acts as a surrogate substrate of mTORC1, and exhibits a change in FRET in response to phosphorylation by mTORC1. Genetically targeting TORCAR to specific subcellular locations further allows for the characterization of spatial compartmentalized mTORC1 signaling. © 2016 by John Wiley & Sons, Inc.